Retorika Jeffrie Geovanie dalam serial Pidato “Sebuah Persembahan untuk Sumatra Barat” - Yunisa Oktavia; Gaguk Rudianto; Yenni Hayati; Dairi Sapta Rindu Simanjuntak; Syafriadi Syafriadi (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2021)
This study aims to analyze the style of language, the language style criticize, efficient use of vocabulary, and persuasive speech delivered in a series of speeches Jeffrie Geovanie a tribute to West Sumatra. The method used is descriptive method and the object of this research is a series of speeches Jeffrie Geovanie a tribute to West Sumatra Padang Ekspres and Singgalang. Based on the analysis we can conclude that the style of language used in the serial Geovanie Jeffrie speech is stylistic hyperbole, personification, epithet, sarcasm, and irony. The author is more inclined to criticize realist style, symbolic, gothic, allegory, and proletarian. In the utilization of the vocabulary used by the author in the form of utilization of scientific vocabulary, popular words, greeting words and idioms. Writers tend to be able to convince and can touch the reader in his speech (speech persuasive).